The impact of different pacing strategies on five-kilometer running time trial performance - Gosztyla, A. E.; Edwards, D. G.; Quinn, T. J.; Kenefick, R. W. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to determine the optimal 1.63-km (1-mile) pacing strategy for 5-km running performance in moderately trained women distance runners. Eleven women distance runners (20.7 +/- 0.8 years, 163.8 +/- 2.0 cm, 57.0 +/- 2.2 kg, 51.7 +/- 1.0 ml/kgmin, 18.9 +/- 0.8% fat, 78.1 +/- 1.4% VO2max at lactate threshold) performed 2 preliminary 5-km time trials on a treadmill to establish baseline 5-km times. The average 1.63-km split pace of the fastest preliminary trial was manipulated for the first 1.63 km of the experimental trials and run either equal to (EVEN), 3% faster than (3%), or 6% faster than (6%) the current baseline average 1.63-km pace for each subject. Ventilation (VE), oxygen consumption (VO2), respiratory exchange ratio, and heart rate were measured continuously. Overall 5-km times were not different (p < 0.05) for the EVEN, 3% and 6% trials finishing in 21:11 (minutes/seconds) +/- 29 seconds, 20:52 +/- 36 seconds and 20:39 +/- 29 seconds, respectively. The fastest time for 8 subjects resulted from the 6% trial and the other 3 subjects' fastest times resulted from the 3% trial. The overall exercise intensity (%V O2max, %VO2max above lactate threshold, VE, and respiratory exchange ratio) of the first 1.63-km split was not different between the 3 and 6% trials, despite the 6% trial being 13 seconds faster than the 3% trial. Based on these findings, initial 1.63-km starting paces of a 5-km race can be 3 to 6% greater than current average race pace without negatively impacting performance. In order to optimize 5-km performance, runners should start the initial 1.63 km of a 5-km race at paces 3-6% greater than their current average race pace.